1991
DOI: 10.1007/978-1-4899-2305-9_5
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of State Space Reconstruction in the Presence of Noise

Abstract: By acceptance of tl_s article, the pubhsher recogmzes thai the U S Government retmnsa nonexcluslve, royalty.free license to pubhsh or reproduce the pUbhsned form of th,S contribution, or lO allow others to do so. for U.S Government purposesThe Los Alamos Nat,or,al Laboratory requests that the publisher identdy this article aswork performedunclertheauspecesoftheUS Department o! Energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Markovian dynamics is rigorously applicable in fundamental physical systems and we capture this ideal with an approach to state space reconstruction of unknown dynamics that maximizes the predictive information of the state. Building upon the results of Takens and others [34][35][36][37][38], who have shown that past information can be leveraged to reconstruct a Markovian state [39], we include previous time points and examine how the predictability improves.…”
Section: Predictive Information For State Space Reconstructionmentioning
confidence: 99%
“…Markovian dynamics is rigorously applicable in fundamental physical systems and we capture this ideal with an approach to state space reconstruction of unknown dynamics that maximizes the predictive information of the state. Building upon the results of Takens and others [34][35][36][37][38], who have shown that past information can be leveraged to reconstruct a Markovian state [39], we include previous time points and examine how the predictability improves.…”
Section: Predictive Information For State Space Reconstructionmentioning
confidence: 99%
“…Some of them consider the chaotic functioning of transport systems. Table 1 contains works on chaos [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], assessing the characteristics of the influence of chaos on the functioning of transport systems [17,[24][25][26][27][28], and the influence of chaos on human behavioral processes and sociodynamics [29][30][31], studying the properties of dynamic systems [32][33][34][35][36][37][38]. Skeptics of applying chaos theory to the study of traffic processes formulate the following common question: "in what way are the chaos and complexity theories specifically applied to urban transport systems?"…”
Section: The Place and Role Of Chaos In Operation Of The Sustainable ...mentioning
confidence: 99%
“…In our situation, the data is permitted to be noisy, and the embedding procedure amplifies noise (Casdagli et al 1991). Therefore, the optimal control approach of approximating the Takens field allows a global, continuous, and nonlinear representation of g to be estimated.…”
Section: Partially Observed Predictionmentioning
confidence: 99%